EFEKTIVITAS PELAYANAN UPT PENGUJIAN KENDARAAN BERMOTOR (PKB) DI KABUPATEN BENGKALIS - Ayu Indah Fajar Waty; Abdul Sadad (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
The Technical Implementation Unit (UPT) of Motor Vehicle Testing (PKB) of the Bengkalis Regency Transportation Service provides services to carry out mandatory testing of motorized vehicles. The services carried out are with the aim of creating effective services so that they can make the service process fast, easy, uncomplicated and precise. In the course of the service process, there are factors that become obstacles in the effort to realize effective services, namely the lack of human resources, especially the testing staff. This study has a purpose, namely to determine the effectiveness of the services carried out by the UPT Motor Vehicle Testing (PKB) Bengkalis Regency. The theoretical concept that the researcher uses is the theory of effectiveness by Steers in Tangkilisan (2005:140-141). By using qualitative research methods and data collection techniques based on interviews, observations and documentation. The results of the research that the authors get are that the implementation of their services still has factors that become obstacles experienced by the UPT Motor Vehicle Testing (PKB) Bengkalis Regency, so that the services implemented have not been effective.